COMPARISON OF CONCRETE AND MODULAR STORAGE PONDS FOR FLOOD CONTROL (CASE STUDY CATCHMENT AREA OF TAMAN RATU CHANNEL) - Thalia Margaretha; Elly Kusumawati Budirahardjo; Ryobi Irfanto (Universitas Udayana, 2024)
Taman Ratu Housing Area which is included in the drainage area of the Taman Ratu connecting channel is almost always flooded with a height variation of 30-60 cm at the peak of the rainy season. One solution of the flood control system according to the principle of sustainable drainage is the utilization of storage ponds. The availability of land, which is dominated by residential areas, motivates the placement of below ground pools with 2 different models, known as concrete pond and modulars. The placement of below ground ponds is also intended to fulfill public facilities into green open space areas. Therefore, this study was conducted to determine the comparison of cost budget plans related to the dimensions of the planned pond. The method that will be used through three stages of research includes hydrological analysis to calculate planned rainfall and planned runoff discharge, followed by hydraulic analysis for the design on the total land area of the development plan of 2015.88 m2, the maximum storage volume obtained with dimensions of 45×45×1.5 m is 421.84 m3 for a 5-year rain return period. The preparation of work unit prices refers to the Minister of PUPR Regulation No.8 of 2023 so that a budget value of Rp 6,256,025,595.86 for concrete pond and Rp 10,518,367,732.62 for modular pond is obtained.